Creating inclusive writing environments in the k-12 classroom reluctance, resistance, and strategies that make a difference - Stockman, Angela (Routledge. Taylor & Francis Group, 2021)
Timely and accessible, this book offers tangible strategies that will help teachers plan and sustain writing workshop experiences that are responsive to the needs of their specific students. Angela Stockman helps teachers understand why some writers may fail to meet their expectations and how to help all writers reach their fullest potential. Organized in three parts, this book reframes common narratives about resistant writers, empowers teachers to design, lead and refine their workshop, and provides a toolkit to do so. The appendices and eResources included provide teachers with instructions for mini-lessons and learning targets that support multimodal composition, perfect for pre-service and in-service teachers"--